Arterial hypertension therapy effectiveness in smokers - D. V. Nebieridze; F. A. Papova; N. S. Ivanishina; A. S. Safaryan; N. L. Vinnitskaya; A. Meliya (Кардиоваскулярная терапия и профилактика)
The review briefly describes the studies on cardiac agents’ effectiveness in smoking patients. Various antihypertensive classes might have different effects in smoking individuals with arterial hypertension (AH). In such patients, medications improving endothelial function might be more effective. At the same time, more evidence is needed to compare various antihypertensive classes’ effectiveness in smokers.